Investigating the Mediating Role of Organizational Dissent in the Relationship Between Organizational Silence and Employee Invisibility in the Imam Khomeini Relief Committee (RA) of Yazd - Mehrizi, Mahmoud; Jalalkamali, Mohammad; Anjomshoae, Zahra; Salajegheh, Sanjar (Digital Transformation and Administration Innovation, 2025)
The present study aimed to investigate the mediating role of organizational dissent in the relationship between organizational silence and employee invisibility in the Imam Khomeini Relief Committee (RA) of Yazd. The research method was descriptive and correlational in nature. The statistical population included all 300 employees of the Imam Khomeini Relief Committee (RA) of Yazd, from whom 152 individuals were selected as the sample based on Cochran’s formula. Standard questionnaires were used, similar to those applied in previous studies. In this study, the validity coefficients for the questionnaires of organizational silence, organizational dissent, and employee invisibility were calculated as 0.909, 0.880, and 0.922, respectively. The reliability coefficients for the questionnaires of organizational silence, organizational dissent, and employee invisibility were calculated as 0.904, 0.937, and 0.918, respectively. Data analysis was conducted using SPSS version 20 and LISREL software. Pearson’s correlation coefficient and structural equation modeling (SEM) were employed for data analysis. The research findings indicated that organizational dissent plays a mediating role in the relationship between organizational silence and employee invisibility in the Imam Khomeini Relief Committee (RA) of Yazd.